2015
DOI: 10.1007/978-94-017-7221-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Improvements and Life Cycle Approaches in Industry Partnerships

Abstract: Prioritizing sustainability as a key strategic focus and managing it similar to other parts of business such as marketing and sales, leading companies have been able to better identify and manage risks as well as enhance brand value and corporate reputation. With industry partnerships a holistic approach is possible. Common metrics, shared value chain data and joint sustainability management form the basis of a successful cooperation. Decision-making processes can be supported effi ciently and infl uence the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It has been indicated from desktop research that business value, leverage, and leadership are drivers for industry LCM initiatives (Radhakrishnan, ). With such initiatives, companies are proposed the opportunity of identifying hotspots, improve products accordingly, and promote them to the market (Saling, ). And as multinational retailers and manufacturers have the possibility to drive sustainable product design throughout their life cycles (Golden, Subramanian, & Zimmerman, ), with collaboration toward shared goals, companies are said to have the possibility to address some of the critical environmental problems the world faces, while also strengthening their own resilience to global challenges (Saling, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been indicated from desktop research that business value, leverage, and leadership are drivers for industry LCM initiatives (Radhakrishnan, ). With such initiatives, companies are proposed the opportunity of identifying hotspots, improve products accordingly, and promote them to the market (Saling, ). And as multinational retailers and manufacturers have the possibility to drive sustainable product design throughout their life cycles (Golden, Subramanian, & Zimmerman, ), with collaboration toward shared goals, companies are said to have the possibility to address some of the critical environmental problems the world faces, while also strengthening their own resilience to global challenges (Saling, ).…”
Section: Introductionmentioning
confidence: 99%
“…With such initiatives, companies are proposed the opportunity of identifying hotspots, improve products accordingly, and promote them to the market (Saling, ). And as multinational retailers and manufacturers have the possibility to drive sustainable product design throughout their life cycles (Golden, Subramanian, & Zimmerman, ), with collaboration toward shared goals, companies are said to have the possibility to address some of the critical environmental problems the world faces, while also strengthening their own resilience to global challenges (Saling, ). Fieldwork, on the other hand, has shown that companies joined in an industry initiative, in response to increased globalized competition, external pressure to demonstrate transparency on environmental and social performance in their product chains, and the increasing effects of climate change on their resources (via e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The basis for comparing each of the indicators Pi of the environmental state of urbanised territories with acceptable values of Pi(add), we use the approach mentioned in [7][8][9][10] to determine the ecological and economic efficiency (EEE) of various products and production processes. This approach is based on the assessment of the state of the environment, possible impacts on human health and ecosystems, as well as material and financial costs in the organisation of technological processes for the production of products throughout its life cycle.…”
Section: Methodsmentioning
confidence: 99%
“…This approach is based on the assessment of the state of the environment, possible impacts on human health and ecosystems, as well as material and financial costs in the organisation of technological processes for the production of products throughout its life cycle. It is based on the scientific works of Peter Saling, Andreas Kicherer, Brigitte Dittrich-Kramer, David R. Shonnard, Isabell Schmidt, Manfred Meurer and others [8][9][10], according to which the term "eco-efficiency" was coined by scientist Stephan Schmidheiny and his colleagues and subsequently approved by the Business Council for Sustainable Development (WBCSD) in his 1992 publication [11]. Initially, it was based on the concept of creating more goods and services while using fewer resources and creating less waste and pollution.…”
Section: Methodsmentioning
confidence: 99%